PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA AUDIOVISUAL TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK PADA PEMBELAJARAN IPAS DI KELAS V UPT SDN NO.78 BALANG KAB TAKALAR - Nurannisa; Aeni Rahman, Syarifah; Wajdi, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low critical thinking skills of students in science lessons due to the dominance of teacher-centered learning and the minimal use of engaging media. The purpose of this study was to determine the effect of implementing the Problem-Based Learning (PBL) model with audiovisual media on students' critical thinking skills. The study used a quantitative approach with an experimental approach, a One Group Pretest-Posttest design, with data collection techniques including tests (pretest and posttest) and observations. Data were analyzed using descriptive statistics and the Wilcoxon test. The results showed an increase in students' critical thinking skills, indicated by an increase in the average score from 60.51 to 75.81, with a significance value of 0.037, indicating a significant effect. These findings indicate that implementing PBL with audiovisual media can improve students' activeness, understanding, and analytical skills. In conclusion, the PBL model with audiovisual media is effective in improving students' critical thinking skills. Consequently, this model can be used as an alternative, innovative learning strategy to improve the quality of science lessons in elementary schools.